(untitled) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
During the second half of the 20th century, and especially in the 1960s, there was a veritable competition among Italians to achieve “symbols of well-being”, which included beach holidays and the practice of amateur film-making. Home movies from the mid-fifties and seventies give rise to a totalizing image of the child, in the absence of whom the family seems to lose interest in recording the holidays at all, to the extent that fathers, mothers and grandparents appear almost exclusively in order to accompany and showcase the little ones.